If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(x+4)-5=2x+6(4+x)
We simplify the equation to the form, which is simple to understand
8(x+4)-5=2x+6(4+x)
Reorder the terms in parentheses
+(+8x+32)-5=2x+6*(4+x)
Remove unnecessary parentheses
+8x+32-5=+2x+6+*(+4+x+)
Reorder the terms in parentheses
+8x+32-5=2x+(+24+6x)
Remove unnecessary parentheses
+8x+32-5=+2x+24+6x
We move all terms containing x to the left and all other terms to the right.
+8x-2x-6x=+24-32+5
We simplify left and right side of the equation.
0x=-3
0=-3
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| -4+7y=17 | | x^2-8x+m=0 | | ((4y-3)/5)-((2y+3)/2) | | 0.50x+0.35(120)=0.25(126) | | -8x-4y=20 | | y^(3/2)-13y^(1/2)+40y^(-1/2)=0 | | 6(6x-4)+5(17-3x)-5(4x+5)=-14 | | 26+x+101=180 | | n/3+3/4=5/6n-1 | | 30x+26=7(4x+5)+2x-9 | | 8m-1=-1-6m-m | | 9+2x=9.25+3x | | X+5/3=-16 | | 6(6x-4)+6(17-3x)-5(4x+5)=-14 | | 14+y=12 | | 5(4y+2)= | | -2m+10=4m-14 | | 0.9x-3.5=0.1 | | -2y-5=3y+20 | | u/3-12=29 | | x^(4/3)-10x^(2/3)=-9 | | 15+x+90=180 | | 32+2y=2(5y+8) | | x^4/3-10x^2/3=-9 | | 2(x-2)/3=2(x+4)/9 | | -7/-84 | | 2+3*(4-2)+6/3+2 | | 1050+600+5x=800+400+8x | | -x^2+4=y | | 3d+8=-4-(3-2d) | | a+5/a2-4-a+4/a2-4a+4 | | (37b-4)-9(4b+4)=-3 |